Effect of flow perfusion conditions in the chondrogenic differentiation of bone marrow stromal cells cultured onto starch based biodegradable scaffolds - Gonçalves, Alexandra (2011)
Cartilage tissue engineering (TE) typically involves the combination of a 3-D biodegradable polymeric support material, with primary chondrocytes or other cell types able to differentiate into chondrocytes. The culture environment in which cell–material constructs are created and stored is an important factor. Various bioreactors have been introduced in TE approaches to provide specific culturing environments that might promote and accelerate cells’ potential for chondrogenic differentiation and enhance the production of cartilage extracellular matrix. The aim of the present study was to investigate the chondrogenic differentiation of goat bone marrow cells (GBMCs) under flow perfusion culture conditions. For that purpose, GBMCs were seeded into starch–polycaprolactone fiber mesh scaffolds and cultured in a flow perfusion bioreactor for up to 28 days using culture medium supplemented with transforming growth factor-b1. The tissue-engineered constructs were characterized after several end points (7, 14, 21 and 28 days) by histological staining and immunocytochemistry analysis, as well as by glycosaminoglycan and alkaline phosphatase quantification assays. In addition, the expression of typical chondrogenic markers was assessed by real-time reverse-transcription polymerase chain reaction analysis. In general, the results obtained suggest that a flow perfusion microenvironment favors the chondrogenic potential of GBMCs.